O Banco Central do Brasil: Institucionalidade, relaç\~oes com o estado e com a sociedade civil, autonomia e controle democrático - Carlos Eduardo Carvalho; Giuliano Contento de Oliveira; Marcelo Balloti Monteiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– The article discusses, based in the theory of Central Bank independence and in the process of formation of the Brazilian monetary authority, the autonomy de facto of BCB inside the State and in face to civil society. Although it is not formally independent, for not disposing of the exclusive prerogative to conduct monetary policy, the BCB acts as if it had full juridical autonomy. In the exercise of that autonomy, the BCB often exceeds the legal limits that should be observed without accountability, as occurred in several recent episodes. Furthermore, the BCB transcend the typical functions of monetary authority and acts as opinion leader and defender of ideas and proposals in areas such as economic policy and juridical. Thus, the relations of BCB with the State and civil society constitute an imperfection of the Brazilian democratic process.
Keywords: E42; E58; H77; 330; Zentralbankunabhängigkeit; Brasilien